(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2024)
Background: Fibro-osseous lesions of the craniofacial complex are represented by a variety of disease processes that are characterized by the nature of ossifications and calcifications. Objective: The purpose of the present study was to see the behavior of non-hybrid and hybrid forms of fibro-osseous lesions. Methodology: This was a cross-sectional study at the Department of Oral & Maxillofacial Surgery of Dhaka Dental College & Hospital, Dhaka (DDCH), Shaheed Suhrawardy Hospital, Dhaka (SSH) and Bangabandhu Sheikh Mujib Medical University (BSMMU) from January 2004 to December 2005. Participants were selected for the study who attended into outpatient and inpatient departments with fibro-osseous lesions during study period, irrespective of age & sex. patients were included who gave informed consent, patients attended with jaw swellings, and radiologically suspecting as fibro-osseous lesions, Biopsy proven fibro-osseous lesions. All patients were advised initially for radiological examination which includes orthopantomogram (OPG), postero-anterior (P/A) view of skull with mandible, lateral view of skull with mandible. After taking informed consent, biopsy was done. The diagnosis was established initially in all cases preoperatively on the basis of an incision biopsy. Postoperatively every surgical specimen was examined carefully and sectioned to examine the nature of tissue within the tumour and examination of the expansion and perforation of the bone was performed. Then histologic examination was done for re-evaluation. Result: A total number of 40 patients were included, in Hybrid form, the growth pattern of majority of swellings were slow at first but later rapid (66.7%) while in Non-hybrid form, it was slow always (61.8%). Maximum site of involvement was in mandible (66.7%) in Hybrid form whereas both mandible and maxilla were equally involved in Non-hybrid form. Hybrid form has significantly higher probability of tenderness in comparison with Non-hybrid form (p <0.001). Tenderness was found in all cases of hybrid form (100%) whereas in Non-hybrid form it was 17.6%. Most of size of Non-hybrid swellings were less than 35 sq. cm but for Hybrid form the size were comparatively bigger. In Non-hybrid form, only 2.9%% of swellings were hard and egg shell crackling but it was 33.3% for Hybrid form and the difference was significant. Recurrent bleeding from the swellings was noted in few cases of hybrid form (33.3%) but it was noted in minority of non-hybrid form (5.9%). Conclusion: In conclusion the behavior of non-hybrid and hybrid forms of fibro-osseous lesions is varied from each other. Journal of National Institute of Neurosciences Bangladesh, July 2023;9(2):136-140